Análisis de la transición de la física clásica a la relativista desde la perspectiva del "cambio conceptual" - Toledo, B.; Arriassecg, I.; Santos, G. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
Interviews about special relativity are realized with students of a Modem Physics course. The results of the interviews’ analysis suggest that conceptual change doesn’t mean a substitution of classic physics conceptions by the relativistic ones but that there is an interactive coexistence of both.